Structural Equation Modeling of the Mediating Role of Experiential Avoidance and Distress Tolerance in the Relationship Between Health Anxiety and Rumination in Patients With Hypertension - Rafiepoor, Amin; Moghimi, Saranaz; Karfeh Raveshi, Fatemeh; Kordmirza Nikoozadeh, Ezzatollah (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: This study aimed to investigate the mediating roles of experiential avoidance and distress tolerance in the relationship between health anxiety and rumination among patients with hypertension.Methods and Materials: This descriptive correlational study was conducted on a sample of 443 patients with hypertension in Tehran, selected using the Morgan and Krejcie sample size table. Standardized questionnaires were used to assess health anxiety, experiential avoidance, distress tolerance, and rumination. Data were analyzed using SPSS-27 for descriptive and inferential statistics, including Pearson correlation, and AMOS-21 for structural equation modeling (SEM) to test the proposed mediation model.Findings: The results indicated significant positive correlations between health anxiety and both experiential avoidance (r = .47, p < .001) and rumination (r = .51, p < .001), while distress tolerance was negatively correlated with all variables (r = –.42 to –.40, p < .001). The SEM analysis revealed that health anxiety had a significant direct effect on rumination (β = 0.31, p < .001), as well as indirect effects through experiential avoidance (β = 0.15, p < .001) and distress tolerance (β = –0.12, p < .001). The overall model demonstrated good fit indices (χ²/df = 2.21, RMSEA = 0.052, CFI = 0.96, GFI = 0.94), confirming the hypothesized mediating model.Conclusion: The findings highlight the importance of experiential avoidance and distress tolerance as psychological mechanisms linking health anxiety to rumination in patients with hypertension. These results underscore the need for clinical interventions aimed at enhancing distress tolerance and reducing avoidance tendencies to alleviate cognitive and emotional burdens in individuals with chronic health conditions.